Cryopyrin-Associated Periodic Syndromes (CAPS): Pathogenesis, Clinical Manifestations, and IL-1-Targeted Therapeutic Strategies - Nadaj, Joanna; Czyżewski, Bartosz; Mariankowska, Anna; Dróżdż, Anna; Posuniak, Weronika; Dorota, Michał; Kozłowski, Karol; Kawa, Oliwia; Żywiec, Wojciech; Milczarek, Cezary (Journal of Education, Health and Sport, 2025)
Cryopyrin-associated periodic syndromes (CAPS) are a group of rare, genetically determined autoinflammatory diseases resulting from gain-of-function mutations in the NLRP3 gene. These mutations lead to constitutive activation of the inflammasome and overproduction of interleukin-1β and interleukin-18, driving chronic systemic inflammation. CAPS encompasses three distinct clinical phenotypes—familial cold autoinflammatory syndrome (FCAS), Muckle-Wells syndrome (MWS), and chronic infantile neurologic cutaneous and articular syndrome (CINCA/NOMID)—which vary in severity and organ involvement. FCAS presents the mildest course with cold-induced symptoms, while CINCA/NOMID is the most severe form, often associated with CNS involvement and progressive sensorineural deficits. Recent advances in understanding CAPS pathophysiology have led to the development of targeted biological therapies aimed at IL-1 inhibition. Anakinra, canakinumab, and rilonacept have demonstrated significant clinical efficacy in reducing systemic inflammation, alleviating symptoms, and improving long-term outcomes, including prevention of organ damage. Early intervention is crucial, especially in severe forms such as CINCA/NOMID, to avoid irreversible complications. The diagnosis of CAPS is based on clinical criteria supported by elevated inflammatory markers and confirmed by genetic testing. This review presents a comprehensive overview of CAPS, covering its molecular mechanisms, clinical manifestations, diagnostic criteria, and current therapeutic strategies, with a focus on IL-1 targeted treatments as the mainstay of care.